Pengaruh Akuntabilitas, Objektivitas Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderasi Study Kasus Pada Kantor Akuntan Publik Di Kota Medan - Ihsan Abdullah (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
This study aimed to analyze the influence accountability, objectivity to the quality audit with the auditor ethics as variable moderation, a case study on public accounting firm in the city of Medan. This research is expected to provide input for the auditors to better maintain the values of accountability and objectivity in order to improve the quality of financial audit. So that the financial statements produced can be a source of information that is accountable for the wearer. The data collection use a questionnaire given to all auditors in public accounting office in the Medan city. Data processed by using multiple regression analysis and test of interaction to obtain the effect of moderating variables on the relationship of independent variables and the dependent variable. From the results of tests carried out showed that the partially accountability effect on audit quality, objectivity does not affect the quality of the audit. Simultaneously accountability of the auditor and objectivity of the auditor affect to audit quality. Auditor ethics did not moderate the relationship between accountability and objectivity of the auditor.